Qualitative investigation into consumer motivations and attitudes towards research shopping in the Georgian market - Khoshtaria, Tornike; Matin, Arian (Management and Administration Journal, 2020)
This study aims to discover different levels of research shopping behavior among Georgian consumers. It adopted a deductive approach by selecting the relevant models of customer behaviour from past papers and testing them in the Georgian market. In order to find the main themes associated with research shopping, five focus groups were held using exploratory and semi-structured questions. The responses were analyzed on the basis of two main customer motivations, utilitarian and hedonistic, in order to find the roots of each factor in consumer`s minds. The results indicate the important roles factors such as the retail sector, price, immediate product availability and staff training play in research shopping behaviour in the market. This research approaches the shopping motivations in a novel manner by connecting those roots to two other elements which are the retail sector and the nature of the retail outlet.